Transfer of clustered and upright fruit characters into two popular chilli cultivars of Tamil Nadu - Reddy, K P M Dhamayanthi, V R K (Journal of Spices and Aromatic Crops, 2001)
Transfer of two agronomically desirable characters from CA-33 and CA-219 to two popular chilli cultivars, G-4 and CO-2, was attempted. The F, hybrids and their segregating population, F2, BC, and BC2 were raised to determine the gene action in respect of the fruit orientation and clustered fruit character. The results revealed that genes responsible for the clustered fruit character are monogenic while, the upright fruit character is digenic, controlled by two genes with dominant and recessive epistasis.